National centralized drug procurement and health care expenditure of households—micro-evidence from CFPS - Li, Xin; Tao, Ran; Jin, Yuning; Li, Na (Frontiers in Public Health, 2024)
Objective This paper utilizes data from the China Family Panel Studies (CFPS) to evaluate the impact of the “4 + 7” National Centralized Drug Procurement (NCDP) on Per Capita Household Health Care Expenditure (PCHHCE). Methods The study applies the Differences-in-Differences (DID) methodology to analyze the effects of NCDP. Various robustness tests were conducted, including the Permutation test, Propensity Score Matching, alterations in regression methodologies, and consideration of individual fixed effects. Results Research indicates that the implementation of NCDP led to a reduction of 10.6% in PCHHCE. The results remained consistent across all robustness tests. Additionally, the research identifies diversity in NCDP effects among various household characteristics, with a more significant impact on households residing in rural regions of China, enrolled in Basic Medical Insurance for urban and rural residents and urban workers, and having an income bracket of 25–75%. Conclusion These findings carry policy implications for the future expansion and advancement of NCDP in China. The study highlights the effectiveness of NCDP in reducing healthcare expenditures and suggests potential areas for policy improvement and further research.